Challenges and Support for Pre-service Teachers’ Virtual Teaching and Practicums: Implications for Bahamian Educational Systems - Hunter-Johnson, Yvonne; Newton, Norrisa; Gardiner-Farquharson, Beulah; Munnings, Janice; Bandelier, Neresa; Butler, Faith; McDonald, Tarah; Swann, Natasha; Edgecombe, Raquel (International Journal of Bahamian Studies, 2021)
Teacher education programmes, nationally and internationally, are unique both at the undergraduate and graduate levels. Specifically, in the Bahamian educational system, they are designed to produce certified K-12 teachers who demonstrate academic and professional excellence in a variety of subject areas. These programmes incorporate a theoretical component and a culminating practical experience that requires pre-service teachers to be evaluated on the quality of their teaching. Normally the culminating experience has been completed in the traditional face-to-face setting. However, the onset of COVID-19 resulted in an immediate imposition of a virtual teaching practicum. This integrated literature review explores the challenges pre-service teachers faced and the support systems they needed during a virtual teaching practicum and addresses implications for practice in a Bahamian setting.